Personal factors influencing female students' condom use at a higher education institution - Danelia M. McCarthy; Rehanna T. Felix; Talitha Crowley (AOSIS, 2024)
Background: South African female students' consistent condom use is low, possibly due to personal factors, such as knowledge about sexual reproductive health, attitudes towards safe sex, risk perceptions and condom use, self-efficacy. Aim: This study aimed to investigate the personal factors that influence condom utilisation among female students. Setting: This study was conducted at a higher education institution in the Northern Cape province in South Africa. Methods: A quantitative, descriptive survey design was used. Three hundred and eighty five participants were selected using convenience sampling. The research instrument was a self-administered questionnaire, and the data were analysed using the Statistical Package for the Social Sciences, version 28. Results: Almost two-thirds (250, 64.9%) of participants used condoms to prevent pregnancy, sexually transmitted infections (STIs), and human immunodeficiency virus (HIV). Although attitudes towards safe sex were generally positive, low risk perceptions were reported. Consistent use of condoms was found in 32.2% (124) of participants, while 45.3% (174) participants used condoms inconsistently or never. A significant finding was that consistent use increased the likelihood of negotiating for a condom with partners by 9.14 times and confidence in putting one on for a partner by 8.05 times. Conclusion: The findings depict average levels of the use of condoms among female students. Prevention efforts should concentrate on educating female students to strengthen condom use and self-efficacy. Contribution: This study, supporting existing literature, suggests that preventative efforts should focus on educating young women about condom use, self-efficacy and encouraging STI conversations with sexual partners.